Contributions of Dar Al-Kotob Al-Ilmiyyah, Beirut in Language and Literature: إسهامات دار الكتب العلمية بيروت فى اللغة والادب - Bano, Dr. saeeda; Fatima, Ammara (Al Khadim Research Journal of Islamic Culture and Civilization, 2025)
Dar al-Kuttab al-Barut is a significant cultural and academic center in Beirut, hosting scholars, students, and researchers. It promotes Arabic literature, organizes events, and supports research projects. Despite facing challenges like funding and preservation due to Lebanon's economic and political instability, Dar al-Kuttab al-Barut’s digitization efforts are a promising step towards preserving Lebanon's rich intellectual heritage and fostering intellectual growth. Its commitment to preserving Arabic manuscripts and rare texts contributes to its preservation efforts. Dar al-Kuttab al-Barut, also known as the Beirut National Library, is a significant cultural and intellectual landmark in Lebanon. Established in the early 20th century, it has become a critical repository of Arabic literature, Islamic jurisprudence (Fiqh), historical records, and modern scholarship. The library's collections cover a broad spectrum of disciplines, including Islamic Jurisprudence (Fiqh) and Theology, Arabic Literature and Poetry, Historical Documents and Regional Archives, and Modern and Contemporary Scholarship. However, Dar al-Kuttab al-Barut faces challenges, particularly with regard to funding and preservation in the face of Lebanon's economic and political instability. The library's commitment to digitizing its collection is a promising step towards preserving its rich cultural heritage and fostering intellectual growth.